LANGUAGE FORM AND FUNCTION OF CARETAKERS FOUND IN NANNY MCPHEE AND THE BIG BANG MOVIE - Aditya Putri Kusuma Andani (Jurnal Penelitian Humaniora, 2015)
This study deals with the form and the function of caretaker speech which is found in caretaker’s utterance in Nanny McPhee and The Big Bang Movie. The objectives of this study are (1) to describe the type of language form of the caretaker and (2) to describe the type of language function of the caretaker found in Nanny McPhee and The Big Bang Movie. The type of this research is descriptive qualitative research. The data of this research are the utterance from the caretaker found in manuscript of Nanny McPhee and The Big Bang Movie. The data collection technique is documentation. The technique of analyzing data are descriptive qualitative. The writer uses the theories from Frank (1972) to analyze the type of language form, and M.A.K. Halliday (1977) to analyze the type of language function. The result of this study shows that (1) there are four types of word: noun, verb, adjective, and adverb; three types of phrase: noun phrase, verb phrase, and adverb phrase; and two types of sentence categorized into two. The first category is based on type, namely: declarative, imperative, interrogative, and exclamatory sentence; the second one by number of full predication, namely: simple, compound, complex, and compound-complex sentence. (2) The writer found 6 types of language function, they are: regulatory function, instrumental function, representational function, personal function, interactional function, and imaginative function.